Cat-life balance. 1 - Otokawa, Akari (Kodansha Comics, 2026)
Everyone at work loves Mamoru, because Mamoru never says no. Replacing lightbulbs, carrying boxes, taking over an impossible client from a retiring colleague... He'll do it all, and it's earned him the nickname "Prince of the Office." This glittering extrovert's opposite at work is Kurone, a quiet woman in another department who soaks up her boss's senseless mood swings with a blank stoicism. After one particularly long day, Mamoru is thrilled to be walking home alone, sipping a beer (because all his colleagues went drinking and left him to work overtime), when he encounters something strange: The usually glum Kurone is in the park, gleefully playing with stray cats. This secret seems silly, but it brings Kurone joy. It's the start of an unlikely relationship that will lead Mamoru to start reflecting on his life and who he really wants to share it with. Is work really all there is, or can he strike a balance with the help of these fluffy new friends--and a human who might become something more?